2018
DOI: 10.1016/j.chom.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The Monocot-Specific Receptor-like Kinase SDS2 Controls Cell Death and Immunity in Rice

Abstract: SUMMARY Programmed cell death (PCD) plays critical roles in plant immunity but must be regulated to prevent excessive damage. The E3 ubiquitin ligase SPL11 negatively regulates PCD and immunity in plants. We show that SPL11 cell-death suppressor 2 (SDS2), an S-domain receptor-like kinase, positively regulates PCD and immunity in rice by engaging and regulating SPL11 and related kinases controlling defense responses. An sds2 mutant shows reduced immune responses and enhanced susceptibility to the blast fungus M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 44 publications
(66 reference statements)
1
75
0
Order By: Relevance
“…43 It is worth mentioning that besides OsRLCK185, several other OsRLCKs have been shown to be involved in regulation of PTI responses and disease resistance in rice. 9,18 Their regulatory relationship with OsCERK1 and OsCNGC9 will be an interesting avenue for future research. In addition, there is also evidence suggesting that the activation of MAPK cascades and anion channel opening are also triggered by pattern recognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 It is worth mentioning that besides OsRLCK185, several other OsRLCKs have been shown to be involved in regulation of PTI responses and disease resistance in rice. 9,18 Their regulatory relationship with OsCERK1 and OsCNGC9 will be an interesting avenue for future research. In addition, there is also evidence suggesting that the activation of MAPK cascades and anion channel opening are also triggered by pattern recognition.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 On the other hand, accumulating evidence indicates PTI-mediated blast resistance also operates in rice. [17][18][19] However, the signaling mechanisms governing PTI-mediated blast resistance in rice remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recent several studies have revealed that ROS are essential for maintaining normal cellular functions, as opposed to having a toxic effect on cells [2]. Even cell death that was previously considered a result from oxidative damage is now thought to be a ROS-mediated physiological pathway for programmed cell death, rather than directly killing the cells [3,4]. Additionally, ROS levels that are too low are cytostatic for cells, whereas ROS levels that are too high are cytotoxic [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several RLCK VII members are immediate downstream signaling components of OsCERK1, including OsRLCK57, OsRLCK185, OSRLCK107, OsRLCK118 and OsRLCK176. OsRLCK118, OsRLCK176, and OsRLCK185 also emerged as substrates of other PRRs, including lysin motif-containing protein (LYP4), LYP6, and SPL11 cell-death suppressor2 [55,76], suggesting that the phosphorylation signaling triggered by PAMPs is transduced from PRRs located on the cell surface to cell cytoplasmic proteins dependent on these RLCKs.…”
Section: Ptms Of Receptor Complexes Initiate Plant Immune Signalingmentioning
confidence: 99%